REVIEW of the scientific article Denys Anatoliiovych Stryzheus “Regarding the Function of the Civil Court of Cassation in the Field of Civil Rights Protection” - Kharkivska, Kateryna (Global Prosperity, 2022)
REVIEW of the scientific article Denys Anatoliiovych Stryzheus “Regarding the Function of the Civil Court of Cassation in the Field of Civil Rights Protection”